Effect of Non-invasive Transcutaneous Electrical Stimulation in Women With Stress Urinary Incontinence: A Prospective Study - Ji-hyun Kim; Hye-seon Jeon; Oh-yun Kwon; Ui-jae Hwang; Eun Young Park; Su-jin Kim (Korean Research Society of Physical Therapy, 2024)
Background: Stress urinary incontinence (SUI) impacts the social, physical, and psychologi-cal well-being and quality of life of the patient. Several techniques exist for its management, including transcutaneous electrical stimulation (TES). Objects: We aimed to demonstrate the effects of TES on ultrasonographic variables and quality of life in women with SUI. Methods: This prospective study recruited 21 women who had been diagnosed with grade 1 or 2 SUI between July 2018 and March 2019. The exclusion criteria were pregnancy and a history of urogenital surgery. All participants were assessed at baseline and 8 weeks after intervention initiation. The bladder neck position (BNP), length of the urethra (LU), funneling index (FI), and rhabdosphincter thickness (RT) were measured. The Incontinence-Quality of Life (I-QOL) was used to assess incontinence-specific quality of life. Statistical significance level was set at p < 0.05. Results: Twenty-one patients with SUI used TES for 8 weeks. BNP and FI significantly de-creased after intervention (p < 0.05). LU, anterior and posterior RT (indicators of external sphincter hypertrophy) significantly increased post-intervention (p < 0.05). The total I-QOL score increased from 64.81 to 71.86 after the intervention (p < 0.05). Conclusion: This intervention improved BNP, LU, FI, RT, and subjective indicators such as quality of life in women with SUI. Therefore, TES can be an effective non-surgical treatment method for improving SUI symptoms and quality of life in these patients.